Material Cost and Benefit Analysis for Dust Injection Technology in EAF Steelmaking Process and EAF Dust Treatment with CaO Addition - Shunsuke Koide; Akira Tsubone; Shusei Kubota; Kazuyoshi Yamaguchi; Tetsuya Nagasaka (Advances in Materials Science and Engineering)
In the electric arc furnace (EAF) steelmaking process, electric arc furnace dust (EAFD) is inevitably generated. The dust injection method is known as one of the effective technologies to reduce the total amount of EAFD generation. In this technology, Zn in the injected dust is enriched in the secondary dust, and Fe is transferred to the slag. In this work, the effect of dust injection technology on the recovered/lost amounts of Zn and Fe is quantitatively evaluated based on the mass balance calculation. Furthermore, in terms of dust and slag treatment costs, the potential of new EAFD treatment technology (the lime addition method) which enables simultaneous Zn and Fe recovery is discussed. By introducing the lime addition method, Zn and Fe can be recovered as resources, and the total income from these sales outweighs the cost of the chemicals used for recovery. This indicates that the treatment costs paid by EAF companies can be significantly low. The dust injection technology reduces the total quantity of dust shipped, but increases the total amount of slag and Fe loss. Therefore, it is necessary to determine the appropriate value of the amount of dust injection by balancing the waste treatment cost and the amount of metal resource recovery.